Rapamycin modulation of p70 S6 kinase signaling inhibits Rift Valley fever virus pathogenesis - Bell, Todd M. (Antiviral Res, 2017)
Despite over 60 years of research on antiviral drugs, very few are FDA approved to treat acute viral infections. Rift Valley fever virus (RVFV), an arthropod borne virus that causes hemorrhagic fever in severe cases, currently lacks effective treatments. Existing as obligate intracellular parasites, viruses have evolved to manipulate host cell signaling pathways to meet their replication needs. Specifically, translation modulation is often necessary for viruses to establish infection in their host. Here we demonstrated phosphorylation of p70 S6 kinase, S6 ribosomal protein, and eIF4G following RVFV infection in vitro through western blot analysis and in a mouse model of infection through reverse phase protein microarrays (RPPA). Inhibition of p70 S6 kinase through rapamycin treatment reduced viral titers in vitro and increased survival and mitigated clinical disease in RVFV challenged mice. Additionally, the phosphorylation of p70 S6 kinase was decreased following rapamycin treatment in vivo. Collectively these data demonstrate modulating p70 S6 kinase can be an effective antiviral strategy.